Situating HIV Stigma in Health Facility Settings: A Qualitative Study of Experiences and Perceptions of Stigma in 'Clinics' among Healthcare Workers and Service Users in Zambia. (May 2022) - Mulubale, Sanny; Clay, Sue; Squire, Corinne; Bond, Virginia; Kasoka, Kasoka; Stackpool-Moore, Lucy; Oraro-Lawrence, Tessa; Chonta, Mutale; Chiiya, Chipo
The study focused on the representations, processes and effects of HIV stigma for healthcare workers living with HIV within health facilities in Zambia. A descriptive study design was deployed. A total of 56 health workers and four service user participants responded to a structured questionnaire (n = 50) or took part in key informant interviews (n = 10) in five high HIV-prevalence provinces. Most participants did not disclose if they were living with HIV, except for four participants who responded to the questionnaire and were selected for being open about living with HIV. Semi-structured interviews were carried out with health workers in key government health facility positions. The questions were standardized and used a Likert scale. Descriptive statistical and thematic analyses were applied to the data. Results show that antiretroviral treatment (ART) has an impact on stigma reduction. Almost half the participants agreed that treatment is reducing levels of HIV stigma. However, fears of exposure of HIV status and labelling and judgemental attitudes persist. No comprehensive stigma reduction policies and guidelines in healthcare facilities were mentioned. Informal flexible systems to deliver HIV services were in place for health workers living with HIV, illustrating how stigma can be quietly navigated. Lack of confidentiality in healthcare facilities plays a role in fuelling disclosure issues and hampering access to testing and treatment. Stigma reduction training needs standardization. Further, codes of conduct for 'stigma-free healthcare settings' should be developed.